SEEKING MEDICAL ATTENTION AMONG JORDANIAN PATIENTS WITH ACUTE MYOCARDIAL INFARCTION - Eshah, Nidal F. (European Scientific Journal, ESJ, 2013)
Background: Significant reduction of mortality rate among acute myocardial infarction (AMI) patients could be achieved by early reperfusion. Successful reperfusion inversely related to the time from onset of AMI symptoms to treatment. Unfortunately, only about 25% of patients with AMI receive reperfusion treatment and the primary reasons for withholding this treatment was the time delay before admitting to hospital. In Jordan, as many other countries there is incomplete understanding for the dimensions of the delay problem in Jordanian community. Purposes: To understanding factors leading to delay seeking treatment among Jordanian AMI patients. Specifically to explore the effects of sociodemographic, clinical, contextual and cognitive factors on delay; as well as identifying factors that predict delay among AMI Jordanian patients. Methods: Comparative descriptive design was used; where convenient sampling technique used to recruit AMI patients within 24-72 hours of admission to coronary care unit. Eligible patients were invited to complete the modified Response to Symptoms Questionnaire. Results: 150 patients were enrolled in the study. The mean delay time for Jordanian AMI patients was nine hours. Only 28% of patients were presented to the hospital within the first hour of symptoms experience. Six factors predicting patient’s delay; those are: living in impoverished area, having low income, being alone at the time of symptoms onset, experienced intermittent symptoms, took medicine to relive symptoms, and worried about troubling others. Conclusion: Jordanian AMI patients have a long delay time before they seek medical treatment. Sociodemographic, clinical, contextual, and cognitive factors were all found to be associated with delay seeking medical treatment. Findings highlighted the need to reduce the time to presentation among Jordanian AMI patients. Such reduction could be achieved by designing and implementing proper interventional programs, as well as improving public awareness of the appropriate responses to AMI symptoms.